Chronic exposure to ivabradine reduces readmissions in the vulnerable phase after hospitalization for worsening systolic heart failure: a post‐hoc analysis of SHIFT. (22nd May 2016) - Komajda, Michel; Tavazzi, Luigi; Swedberg, Karl; Böhm, Michael; Borer, Jeffrey S.; Moyne, Aurélie; Ford, Ian; ,
Abstract: Aims: During the post‐discharge phase following a heart failure hospitalization (HFH), patients are at high risk of early readmission despite standard of care therapy. We examined the impact of chronic exposure to ivabradine on early readmissions in patients hospitalized for heart failure during the course of the SHIFT study (Systolic Heart Failure treatment with the I f inhibitor ivabradine Trial). Methods and results: A total of 1186 of the 6505 randomized patients experienced at least one HFH during the study, and had a more severe profile than those without HFH. Of these 1186 patients, 334 patients (28%) were rehospitalized within 3 months for any reason, mostly for cardiovascular causes (86%), including HFH (61%). Ivabradine was associated with fewer all‐cause hospitalizations at 1 month [incidence rate ratio (IRR) 0.70, 95% confidence interval (CI) 0.50–1.00, P < 0.05], 2 months (IRR 0.75, 95% CI 0.58–0.98, P = 0.03), and 3 months (IRR 0.79, 95% CI 0.63–0.99, P = 0.04). A trend for a reduction in cardiovascular and HF hospitalizations was also observed in ivabradine‐treated patients. Conclusion: We demonstrate in this post‐hoc analysis that chronic exposure to ivabradine reduces the incidence of all‐cause hospitalizations during the vulnerable phase after a HFH. Further studies are needed to investigate if in‐hospital or early post‐discharge initiation of ivabradine could be useful to improve early outcomes in patients hospitalized for HF.